Movement of the South Russian Frontier in the 17th – First Half of the 19th Centuries as the Development of the “Wild Fields” - Valery V. Kanishchev; Yuri A. Mizis (Журнал Фронтирных Исследований)
The authors of the article made an attempt to clarify the concept of frontier, considering it not only in a civilizational sense, but also in a socio-natural context. Particular attention was paid to the movement of the frontier as the development of the “Dykoee Polee” [Rus: steppe, “Wild Fields”], a space not yet plowed by farmers. The purpose of the article was to measure the concrete degree of evolution of the zone of the South Russian frontier during the 17th – 19th centuries in terms of the scale of settlement, population density, and plowing of land. As a result of the study, specific indicators of the development of the “Wild Fields” were obtained: widespread settlement in riverine and upland areas, population density equal to the old regions in the Center of Russia, plowing of more than half of the territory of the former frontier zone, in some “uezds” [Rus.: a group of districts gravitating towards the city] even more than in the traditionally arable central “uezds”. In conclusion, the authors drew attention to the usefulness of studying the nonlinear effects in the development of the “Wild Fields”. In particular, it concerns the economic development of apicultural and other areas, hundreds of which at the end of the 16th – 17th centuries were located in the part of the “Wild Fields” that had not yet been subordinated to the Russian state, as well as the traces of agricultural hike on the territories south of the frontier of the 17th century developed there long before the construction of fortresses and defensive ramparts, – the facts identified recently in collaboration with soil scientists.